The Rice DNA-Binding Protein ZBED Controls Stress Regulators and Maintains Disease Resistance After a Mild Drought - Zuluaga, A. Paola; Bidzinski, Przemyslaw; Chanclud, Emilie; Ducasse, Aurelie; Cayrol, Bastien; Gomez Selvaraj, Michael; Ishitani, Manabu; Jauneau, Alain; Deslandes, Laurent; Kroj, Thomas; Michel, Corinne; Szurek, Boris; et al. (Frontiers in Plant Science, 2020)
Identifying new sources of disease resistance and the corresponding underlying resistance mechanisms remains very challenging, particularly in Monocots. Moreover, the modification of most disease resistance pathways made so far are detrimental to tolerance to abiotic stresses such as drought. This is largely due to negative cross-talks in disease resistance and abiotic stress tolerance signalling pathways. We have previously described the role of the rice ZBED protein containing three Zn-finger BED domains, in disease resistance against the fungal pathogen Magnaporthe oryzae. The molecular and biological functions of such BED domains in plant proteins remain elusive. Using Nicotiana benthamiana as a heterologous system, we show that ZBED localizes in the nucleus, binds DNA and triggers basal immunity. These activities require conserved cysteine residues of the Zn-finger BED domains which are involved in DNA binding. Interestingly, ZBED over-expressor rice lines also show increased drought tolerance. More importantly, the disease resistance response conferred by ZBED is not compromised by drought-induced stress. Together our data indicate that ZBED might represent a new type of transcriptional regulator playing simultaneously a positive role in both disease resistance and drought tolerance. We demonstrate that it is possible to provide disease resistance and drought tolerance simultaneously.